Construcción de un chasis de una silla anfibia con elementos de termofusión - Martínez, Gonzalo (2018)
This paper presents the form of construction of a chassis for the manufacture of a low cost amphibious chair (for the transport and immersion in the water of people with disabilities) carried out with materials of the type of thermofusion. These are commonly used in home water or gas installations and are presented in polypropylene tubes of varying dimensions and wall thicknesses. It is intended in this way, to lower the cost of the same so that they can be used as alternative accessibility elements manufactured in homemade form.